Broad specificity of immune helminth scFv library to identify monoclonal antibodies targeting Strongyloides - Anizah Rahumatullah (Nature Portfolio, 2021)
Abstract Antibodies have different chemical properties capable of targeting a diverse nature of antigens. Traditionally, immune antibody libraries are perceived to be disease-specific with a skewed repertoire. The complexity during the generation of a combinatorial antibody library allows for a skewed but diverse repertoire to be generated. Strongyloides stercoralis is a parasite that causes strongyloidiasis, a potentially life-threatening disease with a complex diagnosis that impedes effective control and treatment of the disease. This study describes the isolation of monoclonal antibodies against S. stercoralis NIE recombinant protein using an immune antibody phage display library derived from lymphatic filaria-infected individuals. The isolated antibody clones showed both lambda and kappa light chains gene usage, with diverse amino acid distributions. Structural analysis showed that electropositivity and the interface area could determine the binding affinity of the clones with NIE. The successful identification of S. stercoralis antibodies from the filarial immune library highlights the breadth of antibody gene diversification in an immune antibody library that can be applied for closely related infections.